PHYSICAL CONDITION TEST OF TRAIL RUNNING ATHLETES IN CENTRAL SULAWESI PROVINCE 2023 PRAPON PREPARATION - Kungku, Christian; Murtono, Tri; Rahmah, Rahmah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Trail running sports are carried out in the mountains or outdoors which have tracks in the form of paths, in the form of earthen stones or mixed with sand and small rocks. Indonesia, especially the Province of Central Sulawesi, has adequate facilities to develop a type of trail running sport. The purpose of this study was to find out how good the physical condition of the trail running athletes in Central Sulawesi Province was in preparation for the 2023 PrePON. The sample in this study was 15 trail running athletes in Central Sulawesi Province. Data collection techniques using tests and measurements. The instruments used in measuring physical conditions in this study were 1) speed (30m run), 2) strength (leg dynamometer), 3) strength (push dynamometer), 4) explosive power (vertical jump), 5) flexibility (sit and reaches), 6) Agility (4x10m shuttle run) 7) Endurance (1600m run). The results showed that there were 0 athletes or 0% in the Very Good category, there were 8 athletes or 53.3% in the Good category, there were 7 or 46.7% in the Moderate category, there were 0 athletes or 0% in the Poor category and there were 0 athletes or 0% in the Less Once category. So it can be concluded that the physical condition of the trail running athletes in Central Sulawesi Province is in the Good category